(NwWEDENIE W ANIZOTROPNU@ UPRUGOSTX (B/s - (N~ERNYH(B, (NkLIMENTIJ fEODOSXEWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1988)
(NbIBLIOGR(B.: (NS(B. 187-190 (85 (NNAZW(B.)s
Keywords: (NuPRUGOSTX(B, (NTEORIQs